MDA and Histologic Profile of Pancreatic Diabetic-Rats Model Administered With Extract of Glycine max (L.) Merr. - Luh Putu Gina; Aulanni'am Aulanni'am; Chanif Mahdi (The Journal of Pure and Applied Chemistry Research, 2016)
Diabetes Mellitus is characterized by leveling up glucose in human blood and affects increasing of free radicals in body as well as leading to cellular oxidative stress. Experimentally, this condition is able to be characterized by increasing malondialdehyde (MDA) level in cell and histological changing in pancreas appearance. Consumption of antioxidant substances was reported able to reduce the MDA quantity as free radicals. Black soybean or Glycine max (L) Merr. was reported contains important antioxidant agents such as anthocyanin and isoflavone. This paper discloses recent investigation on application of black soybean water extract to reduce the MDA level on diabetes mellitus-rat model induced by STZ (DM) and also reports the pancreas histological changing of the DM rats. Investigation revealed that black soybean water extract significantly affect decreasing of MDA level by 4.9%, 27.1% and 45.7% in three different doses theraphy (500, 750, and 1000 mg/kg BW). Histologically, it also clearly indicates repairing of pancreas tissue of the DM rats.